1979
DOI: 10.1002/1097-0142(197901)43:1<269::aid-cncr2820430139>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Aortico‐pulmonary paraganglioma. Report of a case with ultrastructural study and review of the literature

Abstract: The light microscopic and ultrastructural features of an aortico-pulmonary paraganglioma (A-PP) are presented. The tumor was characterized by organoid clustering of neoplastic chief cells to form Zellballen. Argyrophilic granules were demonstrated within chief cell cytoplasm using a modified Grimelus technique. Ultrastructurally, three distinct cell types were present within the tumor: endothelial cells, pericytes and neoplastic chief cells. Membrane-bound neurosecretory granules were present and measured 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…A careful preoperative assessment of the tumor location is crucial and determines the surgical approach. Incomplete resection and high perioperative mortality (5.3% to 9%) have been reported [ 8 , 24 ]. Using ECG gated CT in patients with suspected PGL located intracardially or intrapericardially significantly improves the image quality [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A careful preoperative assessment of the tumor location is crucial and determines the surgical approach. Incomplete resection and high perioperative mortality (5.3% to 9%) have been reported [ 8 , 24 ]. Using ECG gated CT in patients with suspected PGL located intracardially or intrapericardially significantly improves the image quality [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Paragangliomas located in the medial mediastinum arise from paraganglia in the region of the cardiac plexus [ 7 ]. The PGLs localized in the proximity of the ductus arteriosus, the main pulmonary artery and its bifurcation and the adjacent aortic arch are termed “aortic body tumors, aorticopulmonary or aortopulmonary paragangliomas” [ 8 ]. Aortopulmonary paragangliomas are usually asymptomatic [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This over-lap in morphology is even more striking in gangliocytic PG of the small bowel where mixtures of paragangliomatous and carcinoid-islet cell patterns are found (Reed, Daroca & Harkin 1977). This 1978, Gallivan et al 1979, Justrabo et al 1980, Schaefer et al 1980, Hordijk et al 1981, Wetmore et al 1981, Sneige et al 1983) and of paragangliomas in other locations (Grimley & Glenner 1967, Glenner & Grimley 1974, Kahn 1976, Gullotta & Helpap 1976, Damjanov et al 1978, Lack et al 1979b, Robertson & Cooney 1980, Hull et al 1982. Sustentacular cells were present in one case of LP (Sneige et al.…”
Section: Discussionmentioning
confidence: 99%
“…Lack et a/., reported the case of a 15-year-old girl with an aorticopulmonary paraganglioma detected on routine chest X-ray. 4 The authors reviewed 36 cases of paraganglioma at this site and found that 50%1 were detected on routine chest X-ray in asymptomatic patients. Symptomatic patients presented with thoracolumbar sympathetic chain).…”
Section: Case Reportmentioning
confidence: 99%